2010
DOI: 10.1007/s00244-010-9517-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pyrene Bioavailability in Soil by Mild Hydroxypropyl-β-Cyclodextrin Extraction

Abstract: Bioavailability of organic pollutants in soil is currently a much-debated issue in risk assessment of contaminated sites. Ecorisk of an organic pollutant in soil is strongly influenced by the properties of the soil and its contamination history. To evaluate the effect of aging on the availability of pyrene, earthworm (Eisenia fetida) accumulation and chemical extraction by exhaustive and nonexhaustive techniques in soil spiked with a range of pyrene levels (1.07, 9.72, 88.4, 152, and 429 μg g⁻¹ dry soil) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
4
14
0
Order By: Relevance
“…This phenomenon might result from the change in the contamination states of chlorimuronethyl molecules in microsites within the soil matrix (Khan et al, 2011). For instance, chlorimuron-ethyl was redistributed from weaker to stronger sorption sites, which sequestrated or formed bound residues in soil and thus made the extraction very difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon might result from the change in the contamination states of chlorimuronethyl molecules in microsites within the soil matrix (Khan et al, 2011). For instance, chlorimuron-ethyl was redistributed from weaker to stronger sorption sites, which sequestrated or formed bound residues in soil and thus made the extraction very difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Soil was spiked with five different concentrations of phenanthrene (1.12, 8.52, 73, 136, and 335 μg Phe g −1 dry soil) in triplicate according to Cheema et al (2010) and Khan et al (2011) with slight modifications. Briefly, 1-kg air-dried soil was contaminated with the stock solution of phenanthrene and placed in a jar to prepare each independent sample.…”
Section: Soil Spiking and Storagementioning
confidence: 99%
“…Hartnik et al (2008) also developed a HPCD extraction method for the currently used pesticides α-cypermethrin and chlorfenvinphos and found that HPCD extractability correlated well with those of earthworm uptake. Most recently, Khan et al (2011) successfully correlated HPCD extractability and earthworm uptake in pyrene-amended fresh and aged soils.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations